PENGGUNAAN E-JURNAL OLEH MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA DI STKIP PARIS BARANTAI: PENGGUNAAN E-JURNAL OLEH MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA DI STKIP PARIS BARANTAI - Normasunah Normasunah; Sri Juniati; Andi Muhammad Yahya (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The objectives of this study are: 1) Students' perceptions of the Indonesian Language and Literature Education Study Program on the use of e-journals?, 2) The level of use of e-journals for students of the Indonesian Language and Literature Education Study Program. Perception indicators at the perception level by students are utilization, accessibility, convenience, speed, storage, updating, browsing, and security. While the indicators on the level of use are accessibility, speed, frequency of visits. This type of research is descriptive research with a quantitative approach. The technique of collecting is through questionnaires and observation. The results of this study indicate that the results of research on the level of perception of e-journals by students are on a scale of 80 (good). The results of research on student perceptions of the use of e-journals are on a scale of 65 (enough).